'Silver bullet' overdose: the use of dantrolene to treat benzylpiperazine toxicity. Issue 1 (29th January 2014) - Johnston, David
Summary: The number of deaths due to benzylpiperazine toxicity amongst young adults in Northern Ireland and Scotland is increasing, compounded by the growing accessibility to herbal high medication. This case highlights the dangers posed by benzylpiperazine‐containing 'party pill' herbal high recreational agents. Life‐threatening serotonin syndrome resulted in profound central nervous system, haemodynamic and metabolic instability. In the absence of cyproheptadine, dantrolene was successfully used to manage serotonin syndrome although this is not a universally accepted or scientifically proven treatment. Supportive care remains the mainstay of acute management.